Pre-existing chikungunya virus neutralizing antibodies correlate with risk of symptomatic infection and subclinical seroconversion in a Philippine cohort - In-Kyu Yoon; Anon Srikiatkhachorn; Maria Theresa Alera; Stefan Fernandez; Derek A.T. Cummings; Henrik Salje (My University, 2020)
A longitudinal cohort study performed in Cebu City, Philippines found that the presence of pre-existing chikungunya virus (CHIKV) neutralizing antibodies (NAb) was associated with a decreased risk of symptomatic CHIKV infection. However, the relationship between pre-existing NAb and the risk of subclinical seroconversion has not been well described.Data were analyzed from a longitudinal cohort aged 6 months to 83 years who underwent active fever surveillance in Cebu City, Philippines from 2012 to 2014. Participants with a history of fever underwent acute and 3-week convalescent visits with blood collection, and annual visits at baseline, 12 months, and 24 months. Symptomatic CHIKV infections were detected by PCR of acute illness sera. Subclinical seroconversion was defined as a ≥8-fold rise in 80% plaque reduction neutralization test (PRNT80) titer between annual visits without intervening symptomatic infection.Among 854 participants who completed the 12-month visit (year 1) and 765 who completed the 24-month visit (year 2), 25 symptomatic CHIKV infections and 104 subclinical seroconversions occurred among 615 individuals with no detectable pre-year NAb in year 1 and 444 in year 2, while no symptomatic infections and one subclinical seroconversion occurred in those with a pre-year PRNT80 titer ≥1:10. Pre-year PRNT80 titer ≥1:10 was associated with zero relative risk of symptomatic CHIKV infection and 0.018 risk of subclinical seroconversion.The presence of detectable pre-existing CHIKV NAb correlated with a decreased risk of both symptomatic CHIKV infection and subclinical seroconversion. These findings support the potential use of CHIKV NAb titer as a surrogate endpoint of protection from infection for vaccine development.
Keywords: Seroconversion; Subclinical infection; Mosquito-borne diseases and control